Investigating Methane Emissions from China’s Largest Oil and Gas Storage Base Using TROPOMI Observations - Xinxiang Yang; Yuanming Tao; Bohong Wang (Chemical Engineering Transactions, 2023)
Methane is the second largest greenhouse gas after carbon dioxide. In the midstream storage and transportation system of the oil and gas industry, methane leakage and emissions pose a potential climate threat and environmental problem. This study utilized the Tropospheric Monitoring Instrument (TROPOMI) on the Sentinel-5P satellite to examine the atmospheric methane distribution in Zhoushan during August 2022 and to monitor changes in methane concentration. Furthermore, the effects of cloud coverage and oil storage facilities on the quantity of data obtained by the TROPOMI instrument were assessed. The results show that (1) the larger the cloud cover, the smaller the amount of satellite data acquired; (2) days with data volume higher than 200 were selected for quantitative analysis. The methane concentration of the selected area is between 1,529 ppb and 1,945 ppb; (3) in areas with oil storage bases, atmospheric methane concentrations are generally higher, and transportation and loading and unloading of petroleum products may cause methane leakage and emissions. This study helps to deepen our understanding of methane emissions and proposes corresponding environmental protection measures.